2022
DOI: 10.1021/acs.inorgchem.2c00568
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Superconductivity and Nematic Order in Fe1–ySe1–xSx (0 ≤ x ≤ 1; y ≤ 0.1) Crystals by Anion Height Disorder

Abstract: Connections between crystal chemistry and critical temperature T c have been in the focus of superconductivity, one of the most widely studied phenomena in physics, chemistry, and materials science alike. In most Fe-based superconductors, materials chemistry and physics conspire so that T c correlates with the average anion height above the Fe plane, i.e., with the geometry of the FeAs 4 or FeCh 4 (Ch = Te, Se, or S) tetrahedron. By synthesizing Fe 1−y Se 1−x S x (0 ≤ x ≤ 1; y ≤ 0.1), we find that in alloyed c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 67 publications
(114 reference statements)
2
3
0
Order By: Relevance
“…Hence, stronger temperature dependence of γ H outside the nematic region is consistent with the larger gap becoming strongly anisotropic as x is tuned across the NQCP, in agreement with thermal conductivity and specific heat studies [18]. We present T − x phase diagram in figure 4(a), T s and T c are based on the resistivity data (figure 1) and are consistent with a previous report [18,35]. Figure 4(b) shows the slope of the H c2 (T) curve at T c as a function of x.…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Hence, stronger temperature dependence of γ H outside the nematic region is consistent with the larger gap becoming strongly anisotropic as x is tuned across the NQCP, in agreement with thermal conductivity and specific heat studies [18]. We present T − x phase diagram in figure 4(a), T s and T c are based on the resistivity data (figure 1) and are consistent with a previous report [18,35]. Figure 4(b) shows the slope of the H c2 (T) curve at T c as a function of x.…”
Section: Resultssupporting
confidence: 91%
“…Single crystals of Fe y Se 1−x S x (0.10 ⩽ x ⩽ 0.24; y ⩾ 0.9) were grown by the chemical vapor transport method using an eutectic mix of the KCl and AlCl 3 as the transport agent as described elsewhere [33][34][35]. Elemental analysis was obtained from the energy dispersive x-ray spectroscopy (EDX) in JEOL 7600F scanning electron microscopes with about 5% accuracy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reflections shift to higher scattering angles with increasing x , consistent the decrease of the unit cell volume. The nematic transition T s in FeSe, detected via the dip anomaly in ρ­( T ), gradually shifts to T c → 0 as S substitutes for Se in the lattice and vanishes above x = 0.18 (Figure l,m); T c increases weakly up to about 11 K for x = 0.1 (Figure n) which is in agreement with previous observations. The width of the resistivity transition around T c broadens as x increases from 0 and T c reaches its minimum value of 2.1 K for all 0 ≤ x ≤ 1 at x = 0.4 (Figure n,o). For higher S content approaching FeS, T c increases (Figure o), consistent with T c seen in χ­( T )…”
supporting
confidence: 91%
“…Later it became clear that the chemical pressure caused by seleniumsulfur substitution in FeSe 1−x S x did not have the same impact on superconducting properties as the hydrostatic pressure in FeSe. Even for FeSe 1−x S x with 0.2 ≤ x ≤ 1 that have been obtained by the hydrothermal method [11,12], the temperature of the superconducting transition remains below 10 K. It was also demonstrated that disorder suppresses nematicity in FeSe and causes a slight increase in T c [13], which is similar to the behavior of FeSe 1−x S x at low x.…”
Section: Introductionmentioning
confidence: 69%